Biorefinery potential of chemically enhanced primary treatment sewage sludge to representative value-added chemicals - A de novo angle for wastewater treatment. (November 2021) - Jing, Houde; Wang, Huaimin; Lin, Carol Sze Ki; Zhuang, Huichuan; To, Ming Ho; Leu, Shao-Yuan
Graphical abstract: Highlights: CEPT sludge was first time proved as a generic biorefinery feedstock. CEPT sludge was valorized to value-added chemicals via hydrolysis and fermentation. CEPT hydrolysate showed competitive performance over defined standard medium. Carbon neutral potential of CEPT sludge biorefinery were determined. Abstract: Chemically enhanced primary treatment (CEPT) is an emerging sewage treatment strategy due to its high efficiency and small land requirement. CEPT sludge can be easily dewatered and used for energy recovery through incineration. However, with large amount of reusable nutrients (40% organic carbon, 23% lipids, and 17% protein), the value of CEPT sludge may have been underestimated. In this study, the biorefinery potential of CEPT sludge has been proven via production of 28.9 g/L ethanol or 50.3 g/L lactic acid (LA) or 1.43 filter paper unit (FPU)/mL cellulase from 10 g of CEPT sludge experiment. Inhibition on cell growth and potential inhibitors from plasticizers, pharmaceuticals, and surfactants were determined. Nevertheless, production titer was not affected or performed even better than the non-inhibitors controls. CEPT sludge showed significant potential in biochemical conversion, and the related products may offer an opportunity to support wastewater treatment toward sustainability and carbon neutrality.